The effect of seasonal variations on the onset and the relapse of ulcerative colitis - Ahmet TEZEL,; Ülkü DAĞLI,; Çağlar BAYSAL,; Azmi SERİN,; Hülya ÖVER,; Aysel ÜLKER,; Canan ALKIM, (Turkish Journal of Gastroenterology, 2019)
-